2002
DOI: 10.1093/molehr/8.10.893
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional analyses of polymorphisms in the human FSH receptor gene

Abstract: To determine the influence of FSH receptor variants Thr307-Asn680 (TN) and Ala307-Ser680 (AS) on ovarian function, we investigated the frequency of these gene polymorphisms by using restriction fragment length polymorphism analysis and observed their effects on clinical manifestations. In a population of 522 Japanese women, the overall frequency of TN/TN (NN), TN/AS (NS), and AS/AS (SS) was 41.0, 46.9 and 12.1% respectively. In polycystic ovary patients, the NS population was significantly larger when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
228
9
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(270 citation statements)
references
References 20 publications
28
228
9
5
Order By: Relevance
“…Our results are in accordance with the earlier study, where no association of genotypes with gynaecological diseases was observed when the frequency distribution of the genotypes at position 2039 was compared in hypothalamic primary amenorrhea, secondary amenorrhea and POF subjects [18]. Another study has failed to observe differences in the prevalence of FSHR genotype in fertile and infertile women [13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in accordance with the earlier study, where no association of genotypes with gynaecological diseases was observed when the frequency distribution of the genotypes at position 2039 was compared in hypothalamic primary amenorrhea, secondary amenorrhea and POF subjects [18]. Another study has failed to observe differences in the prevalence of FSHR genotype in fertile and infertile women [13].…”
Section: Discussionsupporting
confidence: 92%
“…G −29 A, A 919 G (Thr 307 Ala) and A 2039 G (Asn 680 Ser) polymorphisms have been extensively studied by different investigators. It was reported that the polymorphism A 2039 G is associated with high basal FSH levels in women undergoing Assisted Reproductive Technology (ART) programme [17][18][19][20][21][22]. Recently, we have reported association of FSHR gene polymorphism (A 919 G, G −29 A) with altered ovarian response in subjects undergoing gonadotropin treatment during ART programme [23,24].…”
Section: Introductionmentioning
confidence: 94%
“…This was evident also when PCOS and women with normal ovary were considered as separate subgroups, indicating that the higher percentage of "bestresponders" among heterozygotes in the whole group was not due to a higher prevalence of PCOS among heterozygotes. Interestingly enough, results similar to ours were reported by another study [10], in which heterozygotes required a lower total hMG dose and had more retrieved oocytes. Our data suggest that heterozygosis at position 307 gives a better responsiveness to FSH: this could affect the outcome of the whole IVF treatment, as the "bestresponders" are known to have a high pregnancy chance.…”
Section: Discussionsupporting
confidence: 91%
“…Sudo [10] reported a significant increase in the Ala307Thr frequency among Japanese women with PCOS, 66.7% of which had such allelic variant in comparison to 43.5% of normally ovulating women. In European normogonadotropic anovulatory women (including PCOS), Laven [9] showed a significantly uneven frequency distribution: 20% homozygote Ala307, 57% Ala307Thr and 23% homozygote Thr307.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation